Analysis of the rat hypothalamus proteome by data-independent label-free LC-MS/MS. - Stelzhammer, V; Amess, B; Martins-de-Souza, D; Levin, Y; Ozanne, SE; Martin-Gronert, MS; Urday, S; Bahn, S; Guest, P (2012)
Studies of neuronal, endocrine, and metabolic disorders would be facilitated by characterization of the hypothalamus proteome. Protein extracts prepared from 16 whole rat hypothalami were measured by data-independent label-free nano LC-MS/MS. Peptide features were detected, aligned, and searched against a rat Swiss-Prot database using ProteinLynx Global Server v.2.5. The final combined dataset comprised 21 455 peptides, corresponding to 622 unique proteins, each identified by a minimum of two distinct peptides. The majority of the proteins (69%) were cytosolic, and 16% were membrane proteins. Important proteins involved in neurological and synaptic function were identified including several members of the Ras-related protein family and proteins involved in glutamate biosynthesis.